2016
DOI: 10.3233/nre-161358
|View full text |Cite
|
Sign up to set email alerts
|

Walking with a powered robotic exoskeleton: Subjective experience, spasticity and pain in spinal cord injured persons

Abstract: The overground robot-assisted walking is well accepted by SCI persons and has positive effects in terms of spasticity and pain reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 25 publications
2
93
0
2
Order By: Relevance
“…Exoskeletons have shown to potentially improve ambulatory capacity after a SCI, is safe in usage and is well tolerated by patients [45,49]. A significant disadvantage of the current exoskeletons is the relatively low mean walking speed of 0.26 m/s [52].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exoskeletons have shown to potentially improve ambulatory capacity after a SCI, is safe in usage and is well tolerated by patients [45,49]. A significant disadvantage of the current exoskeletons is the relatively low mean walking speed of 0.26 m/s [52].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with spasticity have shown to experience a reduction in spasticity after training sessions with an exoskeleton [46,49]. An explanation for this could be that the activation of neuronal circuits involved in walking is able to reduce the non-physiological hyperactivation present in spasticity after a SCI [49].…”
Section: Exoskeletonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Repetitive and intensive task-specific training drives beneficial neuroplasticity, thus enhancing functional recovery [56]. Therefore, exoskeletons for motor rehabilitation purposes have emerged in the last decade as a convenient technology that allow multiple, intensive, and more effective sessions of gait training, allowing SCI patients to ameliorate their performance in daily life [56]. Moreover, a study reported that spasticity and pain intensity of SCI patients decreased after one single session of walking assisted by a powered robotic exoskeleton [56].…”
Section: Exoskeletons and Hybrid Exoskeletonsmentioning
confidence: 99%